Enhancement of Oxygen Reduction Performance of Biomass-Derived Carbon through Co-Doping with Early Transition Metal. Issue 15 (1st January 2018) - Dong, Yuanyuan; Zheng, Long; Deng, Yijie; Liu, Lina; Zeng, Jianhuang; Li, Xiuhua; Liao, Shijun
Abstract : We report an early transition metal co-doped carbon catalyst prepared by pyrolyzing a 3D chitosan hydrogel precursor mixed with Zr and Fe species. The catalyst exhibits high activity and pronounced long-term stability for the oxygen reduction reaction (ORR) in both acidic and alkaline media. We find that co-doping with Zr can greatly enhance the catalyst's performance, whereas doping with only Zr results in no improvement. For our optimal sample ZFNC-3-800, its current density at 0.9 V (vs. RHE) could be reach 0.64 mA/cm 2, which is 1.7 times that of FNC-800. Through TEM, XRD and XPS analyses, we find that co-doping with Zr can change the microstructure of the catalyst, immobilize its iron and nitrogen components and modify the distribution of N species in the final catalyst. Importantly, co-doping with Zr leads to the creation of Zr2 FeOx species, contributing to the possible structure of N4-x -Fe-Ox in our ZFNC-3-800 catalyst and enhance its performance. Fe atoms are much more electron-deficient in this structure than in FeNx species and thus favor the adsorption and activation of oxygen molecules. This work is the first to explore co-doping with early transition metals and to reveal their important role in a specific catalyst.